Natural Disaster Aid Distribution System and Meeting the Needs of Case Victims in Padang Pariaman Regency - Yulius, Henny; Dewata, Indang; Heldi, Heldi (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
This study aims to determine the fulfillment of the needs of victims of natural disasters through the implementation of a social assistance distribution system for victims of natural disasters that occurred in Padang Pariaman Regency. This research was conducted using a qualitative descriptive approach that describes the social assistance distribution system for victims of natural disasters with an orientation towards meeting the needs of the victims. It can also be categorized as exploratory research which studies a number of cases of aid distribution towards meeting the needs of victims. Data collection was carried out by direct interviews with officials who were directly involved in the distribution of aid, direct observation to victims of natural disasters, document review, and Focus Group Discussion (FGD). Data analysis, using descriptive-qualitative techniques. The results of the study conclude that the current social assistance distribution system for victims of natural disasters has not yet achieved the goal, namely meeting the needs of victims of natural disasters. Long mechanisms and procedures, incompatible with regional conditions, and the absence of potential synergy of personnel are factors between the ineffectiveness of the social assistance distribution system for victims of natural disasters in Padang Pariaman Regency. The results of the study recommend that in formulating a policy for the distribution of social assistance systems for victims of natural disasters, it should begin with periodic mapping of disaster events and the needs of victims, involving victims as recipients of assistance in accordance with the mandate of Article 26 of Law No.24 of 2007 concerning National Disaster Management. Local governments should be given full authority to implement policies in accordance with regional conditions and disaster characteristics. The granting of this authority should be included in the regional autonomy law regarding the rights of regional governments in the case of natural disaster management, specifically included in local regional regulations.